INTERNALISASI NILAI-NILAI PENDIDIKAN AKHLAK DALAM TRADISI POSUO DI DUSUN ELY JAYA NEGERI LUHU KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT - Yanti, Wa; Kamil, Muslimin (IAIN Ambon, 2023)
This research aims to determine 1) the stages of Posuo tradition implementation, 2) the meanings of denotation, connotation, and myths contained in the Posuo tradition, 3) the moral education values inherent in the Posuo tradition. This research is a qualitative descriptive study with a Semiotic approach, conducted from October 24, 2022, to November 28, 2022. The research location is in the Ely Jaya Hamlet, Luhu Village, Huamual Subdistrict, West Seram Regency. Data collection techniques include observation, interviews, and documentation. In the analysis of data collection, the researcher employs data reduction, data presentation, and drawing conclusions. Based on the research results, it can be concluded that in the Posuo tradition there are: 1) 3 stages of implementation, including; a) Preparation, b) Implementation. The implementation stage consists of several sub-stages, namely pokunde, pebaho, pauncura, panimpa, palego, padole, pasipo, posuo, bhaliana yimpo, landakiana tana, and matana karya. c) Conclusion. 2) The meaning of Posuo tradition symbols. 3) Moral education values in the Posuo tradition include: 1) Moral and Ethical Values during the palego and padole processions. Participants are taught about proper walking and sleeping according to religious and cultural norms. 2) Obedience and discipline, as seen in the rules of the Posuo ritual that must not be violated by participants. 3) Aesthetics, seen when participants are taught how to take care of body and skin beauty. 4) Togetherness, indirectly observed when participants gather in a Posuo room. They engage in all activities together, including eating and sleeping.